Aplicabilidad del proceso de nitritación/desnitritación en el tratamiento de lixiviado de relleno sanitario - Yabroudi, Suher Carolina; Sobrinho, Pedro Alem; Morita, Dione Mari; Queiroz, Luciano Matos; Amaral, Mailer [UNESP] (My University, 2010)
The biological nitritation/denitritation process in the removal of organic matter and nitrogen in a landfill leachate was studied, using an activated sludge sequencing batch reactor. Treatment cycles were formed by an anoxic and an aerobic phases, in which the conditions for oxidation of the influent N load and the prevalence of nitrite concentration at the end of aerobic treatment cycles were determined, as well as the use of organic matter present in the leachate as a carbon source for denitrifying organisms in the anoxic stage. The removal efficiencies of N-NO 2-at the end of the anoxic process (48h) ranged between 14 and 30%, indicating low availability of biodegradable organic matter in the leachate. As for the accumulation of N-NO 2-at the end of the aerobic phase (48h) of treatment cycles, imbalances were not observed, while 100% removal efficiencies of N and specific nitritation rates from 0.095 to 0.158kgN-NH 3/kgSSV per day were recorded, demonstrating the applicability of simplified nitrification in the treatment of effluents with low C/N ratios.
Aplicability of the nitritation/denitritation process in the treatment of a landfill leachate